PENDIDIK DALAM PERSPEKTIF HADIS (SUATU KAJIAN MAUDU’IY) - Suryadi, Ahmad; Ahmad, Arifuddin; Hafid, Erwin (Jurnal Pendidikan Kreatif, 2023)
This article aims: (1) To find out the concept of educators. (2) To find out hadith research about educators. (3) To find out the fiqh al hadis about educators. The hadiths about educators in this study do not meet the validity of the sanad, because the elements of fairness and dhabit of the narrator have not been fulfilled and the continuity of the sanad. The hadith matans contain syadz and illat, this is in accordance with searches on other hadith matans, there are no contradictory hadiths and a few other hadith matans that support this hadith, even though they do not conflict with the verses of the Koran. Given the narration and matan hadith that do not meet the criteria of validity but can be practiced.